Molecularly Imprinted Chitin Nanofiber Membranes: Multi-Stage Cascade Membrane Separation within the Membrane - Shiomi, Kenta; Yoshikawa, Masakazu (Journal of Membrane and Separation Technology, 2016)
Molecularly imprinted nanofiber membranes were fabricated from chitin and print molecule of phenylalanine derivative by simultaneously applying an alternative molecular imprinting and an electrospinning. The D-enantiomer imprinted nanofiber membrane preferentially incorporated the D-enantiomer and selectively transported D-enantiomer and vice versa. The permselectivity was exponentially increased with the increase in the membrane thickness, implying that multi-stage cascade membrane separation was carried out within the nanofiber membrane. The present study led to the conclusion that a molecularly imprinted nanofiber membrane is one of suitable membrane forms for the separation membrane with relatively high flux and permselectivity.